Percutaneous CT Guided Vertebral Biopsy: Anatomy and Technical Considerations - Gala, Kunal Bharat; Shetty, Nitin S.; Janu, Amit Kumar; Shetty, Neeraj; Kulkarni, Suyash S. (Journal of Clinical Interventional Radiology ISVIR, 2021)
In this review article, the authors discuss the anatomy and technical aspects of CT-guided biopsy of vertebral lesions. CT guidance is highly useful for vertebral biopsies, as the anatomy of the spine is complex and varies widely across the levels. Prebiopsy imaging should be reviewed and later correlated with the final histopathological diagnosis. The majority of the spine biopsies are performed under local anesthesia, except those in critical locations and pediatric age groups. The biopsy sample is sent for histopathological analysis and/or microbiological analysis depending on the indications. It is preferable to use a coaxial system for biopsies, so multiple cores can be obtained with a single needle puncture, thus minimizing the negative yield and complications. Complications after image-guided percutaneous biopsy are rare and can be managed easily.
Keywords: spine biopsy; percutaneous biopsy; vertebral lesions